Farm-level economic impact of rice blast: a Bayesian approach - S Varadha Raj; R S Saranya; D Suresh Kumar; M Chinnadurai (Agricultural Economics Research Review, 2023)
This paper assesses the farm-level impacts of rice blast on yield, cost and returns and resource use efficiency in paddy cultivation employing the Bayesian approach. The result shows about 27% less yield and 19% higher cost on the disease affected farms compared to that on unaffected farms, causing a difference of 80% in the net returns. The analysis of resource use efficiency shows a positive impact of plant protection measures on both disease affected as well as unaffected farms. In general, other inputs appear to be sub-optimally utilized.